Prediction of cannibalism in juvenile black rockfish, Sebastes schlegelii (Hilgendorf, 1880), based on morphometric characteristics and paired trials. (7th July 2016) - Xi, Dan; Zhang, Xiumei; Lü, Hongjian; Zhang, Zhixin
Abstract: To predict the occurrence of cannibalism in the culture of larval black rockfish, Sebastes schlegelii, we developed a regression model based on morphometric measurements. First, 156 black rockfish were measured to obtain a theoretical model, that is L T prey = 0.624 L T cannibal + 0.835. Then, 202 trials of paired fish, together with 31 pairs of cannibalistic fish, were used to revise this model, and the practical model was constructed: L T prey = 0.522 L T cannibal + 4.908 ( R ² = 0.99). According to this equation, the threshold of size ratio was deduced, that is 1.30–1.69, which could be used to grade black rockfish by size and remove potential cannibals.